2003
DOI: 10.1002/pon.758
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in chinese cancer survivors

Abstract: To investigate the dimensions and determinants of posttraumatic growth among Chinese cancer survivors, 188 participants were asked to complete a Chinese posttraumatic growth inventory, translated from the Posttraumatic Growth Inventory (PTGI; J Trauma Stress 1996; 9: 455-471), together with the Chinese versions of the Hospital Anxiety and Depression scale, the Mini-Mental Adjustment to Cancer scale, and the General Health Questionnaire. Confirmatory factor analysis showed a different factor structure than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
239
3
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(276 citation statements)
references
References 37 publications
23
239
3
11
Order By: Relevance
“…16,17 Studies have demonstrated these domains to be separate, meaningfully correlated, and observed across cultures. [56][57][58][59][60][61][62][63][64][65] These elements can be measured by the Posttraumatic Growth Inventory (PTGI), a validated instrument.…”
Section: Elements Of Spi-ptgmentioning
confidence: 99%
“…16,17 Studies have demonstrated these domains to be separate, meaningfully correlated, and observed across cultures. [56][57][58][59][60][61][62][63][64][65] These elements can be measured by the Posttraumatic Growth Inventory (PTGI), a validated instrument.…”
Section: Elements Of Spi-ptgmentioning
confidence: 99%
“…More recently, however, this phenomenon, termed posttraumatic growth (Tedeschi & Calhoun, 1996), has been the focus of systematic investigation in the social and behavioral sciences. Posttraumatic growth has been found in samples dealing with a wide variety of crises, including death of a child (Polatinsky & Esprey, 2000), illness of a child (Best, Streisand, Catania, & Kazak, 2001), crime victims (Peltzer, 2000), bombing victims (Maercker & Langner, 2001), cancer survivors (Bellizzi, 2004;Ho, Chan, & Ho, 2004;Weiss, 2004), refugees (Powell, Rosner, Butollo, Tedeschi, & Calhoun, 2003) and those in failed romantic relationships (Tashiro & Frazier, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A catalyst for Calhoun and Tedeschi's (2006) inclusion of sociocultural influences was the differences found in the manifestations of growth across cultures when utilising quantitative methodology (e.g, Ho, Chan, & Ho, 2004;Peltzer, 2000;Znoj, 2005). Subtle differences in the construction of PTG in Australia have also been found quantitatively (e.g., Morris, Shakespeare-Finch, Rieck, & Newberry, 2005) and qualitatively, with increasing emphasis placed on compassion, and little emphasis JOURNAL OF PACIFIC RIM PSYCHOLOGY Alicia Copping, Jane Shakespeare-Finch and Douglas Paton on religious or spiritual growth (Shakespeare-Finch & Copping, 2006;Copping, Shakespeare-Finch & Paton, 2008).…”
Section: Traumamentioning
confidence: 99%
“…Previous research from a range of nations (e.g., Australia, China, South Africa) has shown that these outcomes are the most commonly endorsed dimensions of the Posttraumatic Growth Inventory (Copping et al, 2008;Ho et al, 2004;Peltzer, 2000;Shakespeare-Finch & Copping, 2006;Tedeschi & Calhoun, 1996). Posttraumatic growth is the result of cognitive restructuring in the aftermath of a traumatic experience; however, participants in this sample were more likely to express their personal strength as being a reason for their survival, rather than a result of their experiences.…”
mentioning
confidence: 99%